Genetic architecture of testis and seminal vesicle weights in mice. - Le Roy, I (2001)
Comparisons across 13 inbred strains of laboratory mice for reproductive organ (paired seminal vesicles and paired testes) weights indicated a very marked contrast between the C57BL/6By and NZB/BINJ mice. Subsequently these strains were selected to perform a quantitative genetic analysis and full genome scan for seminal vesicle and testis weights. An F(2) population was generated. The quantitative genetic analyses indicated that each was linked to several genes. Sixty-six short sequences for length polymorphism were used as markers in the wide genome scan strategy. For weight of paired testes, heritability was 82.3% of the total variance and five QTL contributed to 72.8% of the total variance. Three reached a highly significant threshold (>4.5) and were mapped on chromosome X (LOD score 9.11), chromosome 4 (LOD score 5.96), chromosome 10 (LOD score 5.81); two QTL were suggested: chromosome 13 (LOD score 3.10) and chromosome 18 (LOD score 2.80). Heritability for weight of seminal vesicles was 50.7%. One QTL was mapped on chromosome 4 (LOD score 9.21) and contributed to 24.2% of the total variance. The distance of this QTL to the centromere encompassed the distance of the QTL linked with testicular weight on chromosome 4, suggesting common genetic mechanisms as expected from correlations in the F(2). Both testis and seminal vesicle weights were associated with a reduction in the NZB/BINJ when this strain carried the Y(NPAR) from CBA/H whereas the Y(NPAR) from NZB/BINJ in the CBA/H strain did not modify reproductive organ weights, indicating that the Y(NPAR) interacts with the non-Y(NPAR) genes. The effects generated by this chromosomal region were significant but small in size.